Bāyazīd: The Life and Teachings of the Mystic Abū Yazīd al-Basṭāmī (d. ca. 234/848) : Based on the Earliest Sources - Keeler, Annabel, (Middle East and Islamic Studies E-Books Online, Collection 2024., 2025)
Abū Yazīd al-Basṭāmī (d. ca 234/848), popularly known as "Bāyazīd", remains one of the most celebrated yet controversial figures in the history of Islamic mysticism. This in-depth study of his life and teachings is based on the earliest available sources. The book sets out in detail what is known of Bāyazīd's family, his education, his disciples and associates. It explores the distinctive rhetoric that has made some of his sayings so memorable, and shows how his mode of expression adds a sense of urgency, often drama, to quite conventional doctrines of Sufism. Through the varied corpus of his sayings, this study traces Bāyazīd's teachings concerning many aspects of the mystical path, as well as his reflections on God, the Prophet, heaven and hell. Having considered his role as spiritual master, his favourable view of women and his place in the wider community, the study then turns to the controversial side of Bāyazīd: his apparently blasphemous utterances, and his so-called miʿrāj . The book goes on to explore how the two seemingly contradictory sides to Bāyazīd might be reconciled, and finally, provides a brief survey of the extent of his influence on later Sufism and its literature. See Less